Зарубіжний досвід нормативно-правового регулювання ринків фінансових послуг - Глух, Марина Василівна; Анісімова, Марина Федорівна (Державний податковий університет, 2022)
У статті досліджено питання нормативно-правового регулювання ринків фінансових послуг у зарубіжних країнах. Виділено основні моделі регулювання ринків фінансових послуг залежно від кількості суб'єктів регулювання на ринку. Визначено, що Україна використовує інституціональну модель з декількома державними регуляторами. Зазначено перелік країн, які використовують мегарегуляторну модель регулювання ринків фінансових послуг, які об'єднують у собі функції декількох регуляторних органів у сфері регулювання фінансових послуг. Розглянуто принципи регулювання ринків фінансових послуг у країнах Європейського Союзу. Проаналізовано основні Директиви ЄС, що встановлюють питання державного регулювання ринку фінансових послуг та визначають процедуру й умови випуску фінансових інструментів, обмежених в обігу. Окреслено характерні риси сучасного європейського ринку фінансових послуг. Проаналізовано моделі регулювання фінансового ринку, що сьогодні функціонують у провідних європейських країнах, а саме Франції, Німеччині, Великій Британії, Нідерландах, Іспанії. Визначено, що Франція є одним з яскравих прикладів у питанні запровадження схем колективного інвестування. Наголошено, що перевагою регулювання ринків фінансових послуг у Великій Британії є наявність організації, що спеціалізується на скаргах клієнтів фінансових установ, яка має назву Служба фінансового омбудсмена. Встановлено, що особливістю моделі Німеччини є те, що три спеціалізовані федеральні органи, які здійснювали нагляд за діяльністю банків, страхових компаній та інститутів ринку цінних паперів, об'єднано у Федеральне агентство фінансового нагляду. Виділено, що особливістю моделі регулювання ринків фінансових послуг у Нідерландах є пруденційний нагляд за всіма секторами фінансового ринку, віднесений до компетенції Центрального банку Нідерландів. Підсумовано, що для вирішення поточних і довгострокових проблем у сфері правового регулювання ринків фінансових послуг потрібно насамперед розробити нову програму розвитку фінансового сектору в Україні, у межах якої й ринку фінансових послуг, а також адаптувати національне законодавство до вимог європейських стандартів у сфері регулювання ринків фінансових послуг.

The article examines the issues of legal regulation of financial services markets in foreign countries. The main models of regulation of financial services markets depending on the number of subjects of regulation in the market are identified. It is determined that Ukraine uses an institutional model with several state regulators. The principles of regulation of financial services markets in the European Union are considered. The main EU Directives, which establish issues of state regulation of the financial services market and determine the procedure and conditions for issuing financial instruments restricted in circulation, are analyzed. The characteristic features of the modern European market of financial services are outlined. The models of financial market regulation that currently operate in the leading European countries, namely France, Germany, Great Britain, the Netherlands, and Spain, are analyzed. It is determined that France is one of the brightest examples in the implementation of collective investment schemes. It is emphasized that the advantage of regulating financial services markets in the UK is the existence of an organization that specializes in complaints from clients of financial institutions, called the Financial Ombudsman Service. It is established that the peculiarity of the German model is that the three specialized federal bodies that supervised the activities of banks, insurance companies and securities market institutions have been merged into the Federal Agency for Financial Supervision. It is emphasized that the peculiarity of the model of regulation of financial services markets in the Netherlands is the prudential supervision of all sectors of the financial market, which falls within the competence of the Central Bank of the Netherlands. It is concluded that in order to solve current and long-term problems in the field of legal regulation of financial services markets, it is necessary to first develop a new program for financial sector development in Ukraine, including the financial services market, and adapt national legislation to European standards in financial services regulation. The purpose of the article is to study the features of legal regulation of financial services markets in foreign countries and to formulate proposals for improving the legal regulation of financial services markets in Ukraine by harmonizing legislation in this area. The financial services market in Ukraine is in the process of formation. Despite the reform of the legal regulation of the financial services market in Ukraine, a large number of problems remain that need to be addressed immediately. Without a proper level of regulation of the financial services market, the efficient functioning of the country's economy as a whole is impossible. The study of foreign experience of legal regulation of financial services markets makes it possible to identify the main directions of development and improvement of national legislation in this area by identifying priorities and assigning the appropriate range of powers to special entities that carry out such regulation. In view of the above, a detailed study of foreign experience in the legal regulation of the financial services market is relevant. A set of general philosophical, general scientific and special research methods was used. Methods of formal-logical (dogmatic), system-structural, comparative-legal and logical-legal analysis, deduction, induction were used, which allowed to determine the peculiarities of legal regulation of financial services markets in foreign countries. The method of theoretical generalization was also used – to determine the prospects for further improvement of legal regulation of financial services markets. As a result, it is concluded that the creation of the megaregulator is justified the universalization of the financial sector. It is proposed to apply a comprehensive approach to improving the regulation of the financial services market in Ukraine, taking into account European experience, the implementation of which will contribute to more efficient functioning and development of the financial services market. Thus, recent changes in the global financial system lead to changes in the mechanism of regulation of the financial services market. In any case, the further development of the financial services market and the countries of the European Union and other countries, including Ukraine, will have a significant impact on globalization, and therefore a threat in the form of financial destabilization. The most optimal model of state regulation of financial services markets for Ukraine may be the creation of a megaregulator for non-banking financial services markets, leaving the National Bank of Ukraine in the role of banking regulator. Prospects for further research are the need to develop a coherent concept of reforming the system of state regulation of financial services markets and creating a megaregulator in this area, defining the main qualities and characteristics of this body – in particular, its formation, powers, rights and responsibilities, structure.
Keywords: фінансові послуги; ринок фінансових послуг; фінансові установи; державне регулювання; моделі регулювання; макрорегулятори; фінансовий ринок; financial services; financial services market; financial institutions; state regulation; regulation models; macro-regulators; financial market